2019
DOI: 10.3390/urbansci3030086
|View full text |Cite
|
Sign up to set email alerts
|

Green and Blue Infrastructure in Darwin; Carbon Economies and the Social and Cultural Dimensions of Valuing Urban Mangroves in Australia

Abstract: Darwin’s mangrove ecosystems, some of the most extensive and biodiverse in the world, are part of the urban fabric in the tropical north of Australia but they are also clearly at risk from the current scale and pace of development. Climate motivated market-based responses, the so-called ‘new-carbon economies’, are one prominent approach to thinking differently about the value of living infrastructure and how it might provide for and improve liveability. In the Australian context, there are recent efforts to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…The mangroves are threatened by dredging activities, and are exposed to solid waste dumping and wastewater runoff from nearby buildings. However, urban mangrove ecosystems, such as the RAK mangrove wetland, are recognized for a range of ecosystem services including carbon sequestration (Atchison, 2019), improving air quality (Hsieh et al, 2015), and the reduction of urban heat island impact (Lazzarini et al, 2012). Earlier survey testing by the authors showed that only few residents of RAK city are aware of the significance of the mangroves and their ecosystem services, and the threat they are facing from human activities.…”
Section: Introductionmentioning
confidence: 99%
“…The mangroves are threatened by dredging activities, and are exposed to solid waste dumping and wastewater runoff from nearby buildings. However, urban mangrove ecosystems, such as the RAK mangrove wetland, are recognized for a range of ecosystem services including carbon sequestration (Atchison, 2019), improving air quality (Hsieh et al, 2015), and the reduction of urban heat island impact (Lazzarini et al, 2012). Earlier survey testing by the authors showed that only few residents of RAK city are aware of the significance of the mangroves and their ecosystem services, and the threat they are facing from human activities.…”
Section: Introductionmentioning
confidence: 99%